(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
With the notable exception of a crannog along with flint and quartz tools, our knowledge of the archaeology is unsubstantial. Known sites are concentrated in the vicinity of the present village, there is only one site pre-dating the Bronze Age and the medieval period is represented solely by the late medieval church at Kilmory.